PENERAPAN MODEL PEMBELAJARAN TPSQ BERBANTUAN MEDIA ANIMASI UNTUK MEREMEDIASI MISKONSEPSI SISWA MATERI DINAMIKA ROTASI - Zulfa, Wardiati; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research is to determine the effectiveness of Think Pair Square (TPSq) learning model application assisted by animation in remediating students? misconception about rotational dynamics in Grade XI MAN 2 Pontianak. Method of research that is used is pre-experimental design with one group pre-test post-test design. Data was collected by using multiple choice test which consists of three alternative choices completed by reasons with 8 questions. The sample of this study is 36 students of XI IPA 1 which are chosen randomly by using Intact Group technique. Based on data analysis, the average of misconception?s reduction percentage that is got is 44.44% in each concept. Based on Mc Nemar test calculation and continued by Chi Squared test, identified that the average value of , with an average value of  = 26.57. It means that there is significant change of misconception in rotational motion concept. Based on the effect size calculation, the score of ES = 0,485 (medium categorized). Therefore the using of Think Pair Square learning model assisted by animation can remediate student?s misconception about dynamic effectively.Hopefully this study can be used as an alternative to remediate student?s misconceptions. Keywords: Misconception, Think Pair Square, Animation